West Nile Virus: Basic Principles, Replication Mechanism, Immune Response and Important Genetic Determinants of Virulence - Valiakos, George; Athanasiou, Labrini V.; Touloudi, Antonia; Papatsiros, Vassilis; Spyrou, Vassiliki; Petrovska, Liljana; Billinis, Charalambos (IntechOpen, 2013)
None